Sex-Specific 99th Percentile Upper Reference Limits for High Sensitivity Cardiac Troponin Assays Derived Using a Universal Sample Bank - Apple, Fred S; Wu, Alan H B; Sandoval, Yader; Sexter, Anne; Love, Sara A; Myers, Gary; Schulz, Karen; Duh, Show-Hong; Christenson, Robert H (Clinical chemistry (Baltimore, Md.), 2020)
How to select healthy reference subjects in deriving 99th percentiles for cardiac troponin assays still needs to be clarified. To assist with global implementation of high sensitivity (hs)-cardiac troponin (cTn) I and hs-cTnT assays in clinical practice, we determined overall and sex-specific 99th percentiles in 9 hs-cTnI and 3 hs-cTnT assays using a universal sample bank (USB). The Universal Sample Bank (USB) comprised healthy subjects, 426 men and 417 women, screened using a health questionnaire. Hemoglobin A1c (>URL 6.5%), NT-proBNP (>URL 125 ng/L) and eGFR (<60 mL/min), were used as surrogate biomarker exclusion criteria along with statin use. 99th percentiles were determined by nonparametric, Harrell--Davis bootstrap, and robust methods. Subjects were ages 19 to 91 years, Caucasian 58%, African American 27%, Pacific Islander/Asian 11%, other 4%, Hispanic 8%, and non-Hispanic 92%. The overall and sex-specific 99th percentiles for all assays, before and after exclusions (n = 694), were influenced by the statistical method used, with substantial differences noted between and within both hs-cTnI and hs-cTnT assays. Men had higher 99th percentiles (ng/L) than women. The Roche cTnT and Beckman and Abbott cTnI assays (after exclusions) did not measure cTn values at ≥ the limit of detection in ≥50% women. Our findings have important clinical implications in that sex-specific 99th percentiles varied according to the statistical method and hs-cTn assay used, not all assays provided a high enough percentage of measurable concentrations in women to qualify as a hs-assay, and the surrogate exclusion criteria used to define normality tended to lower the 99th percentiles.